Pendidikan Karakter dalam Pengenalan Profesi dan Cita-Cita pada Siswa Tadika Mysarah sebagai Upaya Menumbuhkan Motivasi Belajar di Era Digital - Syalaisha Anaqah Fatihah; Rizka Harfiani (Journal on Education, 2024)
Character education and career introduction at Tadika Mysarah play a crucial role in enhancing students' learning motivation and character development. This study explores how the implementation of these aspects contributes to students' learning motivation and how challenges in the digital era impact this process. Using a descriptive-qualitative method with a literature review approach, the study analyzes various sources including journals, books, and scholarly articles. The findings indicate that introducing careers and aspirations provides students with a clear vision of their future, significantly boosting their motivation to learn. This process helps students connect their learning with potential career opportunities, making them more engaged in their education. However, the implementation of character education and career introduction faces significant challenges, including limited access to technology, digital divide, and the need for adaptation in teaching methods. In the digital era, integrating technology requires training for educators and adjustments to ensure the relevance of educational materials. Despite these challenges, career introduction and aspiration contribute to students' character development by instilling values such as responsibility, hard work, and resilience, as well as enhancing social and communication skills. This research underscores the importance of adapting teaching methods to address digital challenges and maximize the positive impact of character education and career introduction on students' motivation and character development.